Association between serum Klotho concentration and hyperlipidemia in adults: a cross-sectional study from NHANES 2007–2016 - Yan, Shaohua; Luo, Wei; Lei, Li; Zhang, Qiuxia; Xiu, Jiancheng (Frontiers in Endocrinology, 2023)
Objective The Klotho protein is a well-documented anti-aging protein known for its diverse biological functions. Hyperlipidemia is an established independent risk factor for various chronic diseases. However, there is limited understanding of the connection between Klotho and hyperlipidemia. The aim was to assess the association between serum Klotho levels and hyperlipidemia among adults. Methods The study included 11,618 individuals from the NHANES database from 2006 to 2017. Hyperlipidemia was diagnosed following the National Cholesterol Education Program guidelines. Serum Klotho concentration was measured by an enzyme-linked immunosorbent assay kit, and the association between Klotho and hyperlipidemia was assessed by a multivariable logistic regression model. Fitted smoothing curves and threshold-effect analysis were employed to describe nonlinear relationships. Results In our multiple logistic regression models, serum Klotho concentration was significantly associated with hyperlipidemia after adjusting for comprehensive confounders (per SD increment odds ratio (OR): 0.91; 95% confidence interval (CI): 0.86–0.97). Compared to individuals in the lowest Klotho quartile, those in the highest quartile exhibited a substantially decreased prevalence of hyperlipidemia (OR: 0.72; 95% CI: 0.58–0.90). Using a two-segment logistic regression model, we identified a U-shaped relationship between serum Klotho concentration and hyperlipidemia, with an inflection point at 1,365.5 pg/mL. Subgroup analysis did not reveal any potential moderating effects. Conclusion This study revealed an inverse relationship between Klotho levels and hyperlipidemia. Further investigation is warranted to explore the underlying mechanism between serum Klotho and hyperlipidemia.